Ovrednotenje premoženja znamke Slovenije kot turistične destinacije v očeh Nemcev in Hrvatov - Konečnik Ruzzier, Maja (Naše gospodarstvo, 2006)
The paper presents the concept of customer-based brand equity and its application to our analyzed entity: a tourism destination. The introduced concept of customer-based brand equity for a tourism destination completes previous research findings in this area because it investigates the element of awareness and destination loyalty in addition to the image (and perceived quality) of the tourism destination. The empirical part of the paper analyses the brand Slovenia from the points of view of Germans and Croatians. The results indicate that Croatian respondents have a better perception of Slovenia as a tourism destination than German respondents.
Keywords: Slovenia; Slovenija; tourism; turizem; blagovne znamke; kvaliteta; trženje